2019
DOI: 10.3389/fpls.2018.02003
|View full text |Cite
|
Sign up to set email alerts
|

TaSnRK2.9, a Sucrose Non-fermenting 1-Related Protein Kinase Gene, Positively Regulates Plant Response to Drought and Salt Stress in Transgenic Tobacco

Abstract: Sucrose non-fermenting 1-related protein kinase 2 (SnRK2) family members play crucial roles in plant abiotic stress response. However, the precise mechanism underlying the function of SnRKs has not been thoroughly elucidated in plants. In this research, a novel SnRK2 gene, TaSnRK2.9 was cloned and characterized from common wheat. The expression of TaSnRK2.9 was upregulated by polyethylene glycol (PEG), NaCl, H2O2, abscisic acid (ABA), methyl jasmonate (MeJA), and ethrel treatments. TaSnRK2.9 was mainly express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(38 citation statements)
references
References 62 publications
0
30
0
Order By: Relevance
“…The expression of GhSnRK2.6 was shown to be up-regulated under salt conditions, and further demonstrated that GhSnRK2.6 improved salt tolerance in transgenic upland cotton and A. thaliana [48]. In addition, TaSnRK2.9 positively regulates the response of transgenic tobacco plants to drought and salt stress [30]. The EgrSnRK2.6 clusters with these gens, but was up-regulated to two-fold with increasing salt concentrations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The expression of GhSnRK2.6 was shown to be up-regulated under salt conditions, and further demonstrated that GhSnRK2.6 improved salt tolerance in transgenic upland cotton and A. thaliana [48]. In addition, TaSnRK2.9 positively regulates the response of transgenic tobacco plants to drought and salt stress [30]. The EgrSnRK2.6 clusters with these gens, but was up-regulated to two-fold with increasing salt concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…PtSnRK2.5 and PtSnRK2.7 positively regulate plant responses to salt stress [28]. The overexpression of TaSnRK2.3 , TaSnRK2.4 , TaSnRK2.7 and TaSnRK2.8 in A. thaliana was reported to enhance plants tolerance to salt and other stresses [29,30]. Recent studies have shown that TaSnRK2.9 improved salt and drought stress tolerance through detoxification of (reactive oxygen species) ROS [30].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The activities of POD and SOD, H 2 O 2 content, and GSH level in soybean hairy roots were measured as described previously [63,64]. In brief, total proteins were extracted using the vegetable protein extraction kit (KeyGene BioTECH, Nanjing, China) and quantified using a BCA protein assay kit (KeyGene BioTECH).…”
Section: Methodsmentioning
confidence: 99%
“…Several other studies have shown that overexpression of different drought responsive genes confers greater drought tolerance in transgenic wheat including the genes AtHDG11 (Li et al, 2016), TaCIPK23 (Cui et al, 2018), TaBZR2 (Cui et al, 2019), TaWRKY2 (Gao et al, 2018), TaWRKY1, and TaWRKY33 (He et al, 2016), and TaPYL4 (Mega et al, 2019). Interestingly, TaSnRK2.9, which is a sucrose non-fermenting 1-related protein kinase gene cloned from bread wheat, elevated ABA content in tobacco (Nicotiana tabacum) resulting in greater drought tolerance (Feng et al, 2019). Therefore, both gene editing and genetic engineering show promise in terms of achieving drought tolerance in wheat.…”
Section: Genome Engineering Techniquesmentioning
confidence: 99%